Strategy for Penetrating Global Regulatory Barriers: A Case Study of Non-Tariff Measures for Biopharmaceutical plant MSMEs in Lumajang - Kukuh Judy Handojo; Sudarmiatin Sudarmiatin; Heri Pratikno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
A MSMEs in Indonesia has recently contributed to national exports by 15,7% compared with Thailand that has reached 29 %, so substantial revision are required to make sure that increasing contribution which ultimately will give positive impact toward the economy overall, because almost 90 % of human resource work in MSMEs sector with nature resource and other plentiful resources. The main problem that is commonly found by MSMEs is to optimize the available resources as well as fulfill the required standards that have established and required regulation in order to ensure the resulting product is accepted by the market and to comply with the regulation that has been established by the regulator. Indonesia as the second biggest country in the world has biodiversity certainly offers benefits that hard to imitate by other country in producing biopharmaceutical plants product, therefore it offers competitive potential in the global market, however market penetration by MSMEs biopharmaceutical plants sector commonly discontinued regarding with technical barriers to trade (TBT). This study is based on a case study that aims to analyze main challenges in fulfillment of international certification and to formulate adaptation strategy for MSMEs. By conducting through a descriptive qualitative method with case study approaches, the result of study indicates that high compliance costs, registration procedural complexity from the source and destination country, as well as the inconsistency of raw material quality became the main barriers. The proposed strategy including group certification model, CPOTB standard harmonization, and the utilization of integrated government assistance schemes will provide real contribution in assisting MSMEs fulfilling global market requirements.